We are given that `h(t)=12sin(pi/6-t)` and we are asked to find t so that h(t)=6.

`6=12sin(pi/6-t)`

`sin(pi/6-t)=1/2`

`sintheta=1/2 ==> theta=pi/6 +-2kpi` or `theta=(5pi)/6 +- 2kpi`

So `pi/6-t=(pi/6+-2kpi)` ==> `t=pi/6-pi/6+-2kpi=2kpi`

`pi/6-t=((5pi)/6+-2kpi)` ==> `t=pi/6-(5pi)/6+-2kpi=(-2pi)/3+-2kpi`

The first instance after t=0 that the height is 6 is at `t=-(2pi)/3+2pi=(4pi)/3`

So `t~~4.19"min"`

The graph:

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We are given that `h(t)=12sin(pi/6-t)` and we are asked to find t so that h(t)=6.

`6=12sin(pi/6-t)`

`sin(pi/6-t)=1/2`

`sintheta=1/2 ==> theta=pi/6 +-2kpi` or `theta=(5pi)/6 +- 2kpi`

So `pi/6-t=(pi/6+-2kpi)` ==> `t=pi/6-pi/6+-2kpi=2kpi`

`pi/6-t=((5pi)/6+-2kpi)` ==> `t=pi/6-(5pi)/6+-2kpi=(-2pi)/3+-2kpi`

The first instance after t=0 that the height is 6 is at `t=-(2pi)/3+2pi=(4pi)/3`

So `t~~4.19"min"`

The graph:

Note that `y=12sin(pi/6-t)=12sin(-(t-pi/6))`

The 12 is the amplitude. The negative 1 inthe function reflects the sin wave across teh y-axis, and the `pi/6` is a phase shift of `pi/6` units to the right.